Renovationist Church Episcopate in USSR in 1941-1945: Transformations of Political Views - I. V. Petrov (Научный диалог, 2019)
The article is devoted to the problem of political preferences of the renovationist episcopate in the USSR in 1941-1945. The author notes that, contrary to the popular opinion about the Pro-Soviet positions of all the bishops-renovationists in the temporarily occupied by the Nazis territory of the RSFSR, many of them were able to successfully return to their ministry, took the previously empty Episcopal chairs and actively carried out anti-Soviet propaganda. It is emphasized that in the territory free from occupation, the Renovationism leaders from the first days of the war stood actively on the Pro-Soviet position, called on believers to fight the enemy. The author proves that initially the Soviet government provided the Church with the same support as the sergians, and only after September 1943 a smooth preponderance of state preferences in favor of the “old churchmen” begins. Attention is paid to the fact that in the conditions of the end of the war many active figures of the Renovationist movement for a long time successfully competed with the Moscow Patriarchate, and then, when it was necessary to reunite with the Russian Orthodox Church, took all possible steps to preserve their own influence. The presented author’s development is based on the materials of Russian archives, as well as modern scientific literature devoted to the problems of the history of religion during the Great Patriotic war and the study of divisions within the Russian Orthodoxy.